1994
DOI: 10.1091/mbc.5.3.339
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal growth factor receptor-dependent stimulation of amphiregulin expression in androgen-stimulated human prostate cancer cells.

Abstract: Amphiregulin is a heparin-binding epidermal growth factor (EGF)-related peptide that binds to the EGF receptor (EGF-R) with high affinity. In this study, we report a role for amphiregulin in androgen-stimulated regulation of prostate cancer cell growth. Androgen is known to enhance EGF-R expression in the androgen-sensitive LNCaP human prostate carcinoma cell line, and it has been suggested that androgenic stimuli may regulate proliferation, in part, through autocrine mechanisms involving the EGF-R. In this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
24
0

Year Published

1996
1996
2004
2004

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(26 citation statements)
references
References 22 publications
2
24
0
Order By: Relevance
“…It has been reported that 5a-DHT does not change intracellular levels of EGF. 44 Although upregulation in EGFR has been detected when these cells were cultured in the presence of androgens, 45,46 it has been shown that 5a-DHT-stimulated LNCaP cell proliferation is not inhibited by the addition of anti-EGFR neutralizing monoclonal. This suggests that autocrine activation of EGFR is absent in androgen stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that 5a-DHT does not change intracellular levels of EGF. 44 Although upregulation in EGFR has been detected when these cells were cultured in the presence of androgens, 45,46 it has been shown that 5a-DHT-stimulated LNCaP cell proliferation is not inhibited by the addition of anti-EGFR neutralizing monoclonal. This suggests that autocrine activation of EGFR is absent in androgen stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…These data reveal differential behaviour of normal versus tumoral breast epithelial cells in regard to the action of AR and demonstrate that, in a number of cases, AR might play a significant role in tumour progression through the regulation of the PA/plasmin system. Whereas the expression of AR in a variety of both nontransformed and tumoral cells appears to be stimulated in the presence of EGF (Normanno et al, 1994b;Sehgal et al, 1994), the potential regulation of AR by growth factors in normal breast epithelial cells has never been examined. Because previous studies suggest that dysregulated expression of AR may be a component of mammary tumorigenesis we proposed to analyse and to compare the regulation of amphiregulin gene expression and protein secretion by EGF in normal and tumoral breast epithelial cells.…”
mentioning
confidence: 99%
“…AR is expressed in several tissues, such as human ovary, placenta, lung, kidney, stomach, colon and breast (Johnson et al, 1992;Lejeune et al, 1993). Increased evidences strongly suggest that AR may function as a potential autocrine growth factor in tumoral as well as in their counterpart normal cells, such as prostatic (Sehgal et al, 1994), colonic (Johnson et al, 1992;Normanno et al, 1995), and mammary epithelial cells (Li et al, 1992;Normanno et al, 1994a, b). Moreover, overexpression of AR has been detected in several oestrogen-responsive and -unresponsive breast cancer cell lines as well as in approximately 80% of human primary breast carcinoma (Martinez-Lacaci et al, 1995;Visscher et al, 1997).…”
mentioning
confidence: 99%
“…AR is commonly overexpressed in human malignancies of the colon (22,28), stomach (29 -31), breast (32), and in the pancreas, overexpression correlates with reduced patient survival (26,33). In vitro, AR has been shown to function in an autocrine manner to drive the proliferation of malignant cells of the colon (22), breast (24), cervix (34), prostate (35), and pancreas (26,27).…”
mentioning
confidence: 99%